2016
DOI: 10.3168/jds.2016-11088
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Effect of maternal heat stress in late gestation on blood hormones and metabolites of newborn calves

Abstract: Maternal heat stress alters immune function of the offspring, as well as metabolism and future lactational performance, but its effect on the hormonal and metabolic responses of the neonate immediately after birth is still not clear. The objective of this study was to investigate the blood profiles of hormones and metabolites of calves born to cows that were cooled (CL) or heat-stressed (HS) during the dry period. Within 2 h after birth, but before colostrum feeding, blood samples were collected from calves [1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
(22 reference statements)
3
8
0
3
Order By: Relevance
“…Additionally, heat stress during gestation can compromise placental development, which results in fetal hypoxia, malnutrition, and eventually fetal growth impedance (Tao et al, 2012). Maternal hyperthermia also desensitizes a calf's stress response and alters the fetal development by reducing the secretion of insulinlike growth factor-I, prolactin, and insulin (Guo et al, 2016). Additionally, maternal heat stress during late gestation alters blood metabolite profile and increases non-insulin dependent glucose uptake (Monteiro et al, 2016a) which eventually negatively affects the survival of calves (Monteiro et al, 2016b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, heat stress during gestation can compromise placental development, which results in fetal hypoxia, malnutrition, and eventually fetal growth impedance (Tao et al, 2012). Maternal hyperthermia also desensitizes a calf's stress response and alters the fetal development by reducing the secretion of insulinlike growth factor-I, prolactin, and insulin (Guo et al, 2016). Additionally, maternal heat stress during late gestation alters blood metabolite profile and increases non-insulin dependent glucose uptake (Monteiro et al, 2016a) which eventually negatively affects the survival of calves (Monteiro et al, 2016b).…”
Section: Resultsmentioning
confidence: 99%
“…The consequences of this thermal stress are not only manifested during periods of high ambient temperature, but present long-lasting effects on the fertility of the dairy cow (García-Isperto et al, 2006, 2007. Recent evidence shows that offspring from pre-partum heat-stressed cows have impaired cellmediated immune function and compromised passive immunity (Tao & Dahl, 2013), as well as a reduced secretion of prolactin, insulin and insulin-like growth factor (Guo et al, 2016), which could be linked to the occurrence of stillbirths. A missing piece of the stillbirth puzzle, thermal stress during the peripartum period, has not been adequately investigated relative to stillbirth incidence.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the increase in body temperature caused by thermal stress has adverse outcomes on reproductive hormones (Hansen & Arechiga, ). Additionally, maternal hyperthermia alters the foetal development by reducing the secretion of insulin‐like growth factor‐I, prolactin and insulin (Guo et al, ). It has been demonstrated that repeat breeding syndrome and infertility increase during summer months (BonDurant et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Але неможливо стверджувати, що плід зовсім не підлягає зовнішньому впливу. Відомо, що рівень годівлі та склад раціону, хвороби і функціональна напруга організму матері відображаються на розвитку плоду -його величині, здоров'ї, тривалості пренатального розвитку і життєздатності (Wolfenson et al, 2000;Hansen et al, 2002;Tao et al, 2012;Merlot et al, 2013;Strong et al, 2015;Guo et al, 2016;Monteiro et al, 2016;Azzam et al, 2017;Chernenko et al, 2017).…”
Section: вступunclassified